PENERAPAN CONTEXTUAL TEACHING AND LEARNING DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS IV SEKOLAH DASAR - Yulia Anggraini; Fida Rahmantika Hadi; Titik Isdarwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Implementation of learning that applies the model contextual teaching and learning with approach culturally responsive teaching can improve students' cognitive learning outcomes. The learning process carried out integrates culture and relates the material in a real way to the surrounding environment so that the understanding gained is meaningful. The purpose of this research is to (1) describe the influence of learning models contextual teaching and learning with approach culturally responsive teaching on cognitive learning outcomes, (2) improving students' cognitive learning outcomes in science and science subjects with Indonesian Cultural Rich material. The research method used is a qualitative descriptive method with the type of classroom action research. This research uses a research design Kemmis and Mc. Teggart with 3 learning cycles, each cycle 2 meetings. The activities of each cycle include planning, action, observation and reflection activities. This research was carried out in the even semester of the 2024/2025 academic year, February-April. The subjects of this research were students in class IV-C at SDN 01 Taman, Taman District, Madiun City with a total of 20 students consisting of 8 male students and 12 female students. The object of the research is the cognitive learning outcomes of class IV-C students. The data collection techniques used are observation, interviews, tests and documentation. The results of this research showed that there was a significant increase, namely in the pre-cycle by 60%, cycle 1 by 70%, cycle 2 by 75% and cycle 3 by 90%. Increasing learning outcomes is said to be successful if 80% of students have completed the learning objective achievement criteria (KKTP) of 75. Thus, the use of the learning model contextual teaching and learning with approach culturally responsive teaching can improve the cognitive learning outcomes of class IV-C students at SDN 01 Taman Kota Madiun.